The Impact of The Us–Israel Vs Iran War on Global Macroeconomic Stability in 2026 (Analysis of Inflation and Economic Policy Responses Amid The Energy Crisis) - Supaino Supaino; Diena Fadhilah; Rehulina Bangun; Sally Maya Vida (International Journal of Economics and Management Sciences, 2026)
This study aims to analyze the impact of the geopolitical conflict between the United States, Israel, and Iran in 2026 on global macroeconomic stability and climate change dynamics. Using a qualitative approach through a Systematic Literature Review (SLR), this research synthesizes findings from various international journal articles, reports, and academic sources. The results indicate that the conflict has significantly disrupted global energy markets, leading to a sharp increase in oil and gas prices. This energy shock has triggered global inflationary pressures, reduced purchasing power, and increased economic uncertainty across both developed and developing countries. Furthermore, monetary tightening policies implemented to control inflation have created trade-offs with economic growth, increasing the risk of global recession. On the fiscal side, government interventions such as energy subsidies have helped mitigate short-term impacts but have raised concerns about long-term fiscal sustainability. In addition, the energy crisis has slowed the transition toward renewable energy, thereby exacerbating climate change risks. The study highlights the interconnectedness between geopolitical conflict, macroeconomic instability, and environmental sustainability. Therefore, coordinated global policies and integrated economic strategies are essential to address these multidimensional challenges effectively.